PRODUKSI BAHAN BAKAR CAIR DARI LEMAK SAPI MENGGUNAKAN KATALIS ZEOLIT DENGAN METODE PIROLISIS - Lestari, Sutini Pujiastuti; Aswan, Arizal; Effendy, Sahrul; Febriana, Ida; Ramadhana. S, Safira Eva; Safitri, Widi; Shaskia, Bekka Alta (Politeknik Negeri Sriwijaya, 2020)
Beef tallow is structurally a monoalkyl ester of long chain fatty acids similar to vegetable oil which are widely used as raw materials for biofuel production. The processing of beef tallow into liquid fuel is from pyrolisis process of the catalytic cracking method with 1%w/w and 5% natural zeolite catalyst. The purpose of this research is to get the best operating condition that produce the largest %yield of liquid fuel with temperature range 280-320oC and time range 60-140 minutes. The result shown that the optimum temperature is 320oC using 5% catalyst with product yield of 12.4206 %. The optimum time operation is 100 Minutes using 5% catalyst with product yield 11.51%Also the best operating condition using 1% catalyst are at temperature of 320°C and 60 minutes with11.86% of yield. Physical character from this research aredensity, kinematic viscosity,and flash point shown that liquid fuel product obtain solar. Chemical compound in liquid fuel of this research are 18.26% of gasoline fraction (C7–C11) and 41.33% of kerosene/diesel (C12–C19) for 1% catalyst and 40.67% of gasoline fraction (C7–C11) and 47.11% of kerosene/diesel (C12–C19) for 5% catalyst.